Marketing digital para incrementar las ventas de la empresa Nederagro, ciudad Guayaquil - Lino Marcillo, Julio César (2017)
This research proposal proposes a marketing strategy based on the 4F model to achieve a significant increase in the level of interactivity with the customers of Nederagro. In terms of instrumentation, tools and mechanisms as components of social media marketing, it is associated with the marketing process of the company Nederagro and offer a direct channel of orders, which minimizes the time and ordering process for distributors and points of sale Of the company Nederagro. In addition, this proposal is justified in achieving the increase in sales of agrochemical products, since the virtual catalogs will be published in digital media through the internet……….